The Risk Management and Value Engineering: Mitigating Challenges in Construction - Waheed, Muhammad (MultiTech Publisher, 2024)
Value Engineering is a management technique crucial in construction for enhancing value and reducing costs. Unlike mere cost cutting, Value Engineering aims to improve functionality by minimizing energy consumption in terms of manpower, materials, and machines. Multidisciplinary teams of engineers, influencing the design process, enhance Value Engineering benefits. It's highly effective in identifying and eliminating unnecessary costs across building design, construction, operations, and maintenance. Value Engineering involves three main stages: Pre-Study, Job Plan, and Post-Study. This literature review delves into how Value Engineering principles are applied in building projects to achieve superior quality at lower costs.